Electrophysiological Characteristics of Dorsal Raphe Nucleus in Tail Suspension Test - Zhou, Liuchang; Liu, Dan; Xie, Zedan; Deng, Di; Shi, Guoqi; Zhao, Jinlan; Bai, Shasha; Yang, Lei; Zhang, Rong; Shi, Yafei (Frontiers in Behavioral Neuroscience, 2022)
Dorsal raphe nucleus (DRN) is the most concentrated brain region for serotonin, which is closely related to depression-like behaviors and is modulated by local GABAergic interneurons. Although serotonin neurons are known to be fired with struggling behavior in tail suspension test (TST), the exact electrophysiological characteristics are still unclear. Here we combined in vivo electrode recording and behavior test to explore the mice neuron electrophysiology in DRN during TST. We observed that gamma oscillation was related to despair-like behaviors while burst fraction was crucial for survival-like behaviors. Furthermore, by using optogenetics to identify parvalbumin positive (PV+) and serotonin transporter positive (SERT+) neurons, we found SERT+ neurons were almost survival units, although acutely activated whole SERT+ neurons in DRN by optogenetics or chemo genetics would not reverse behavior states during TST. Interestingly, identified PV+ neurons include two subtypes, despair and survival units. These results suggest that incorporating electrophysiological characteristics in despair-like behavior studies can provide new insight into anti-depression target and GABAergic interneuron is a complex key hub to the coding and regulation of local neural network.